Future vegetation–climate interactions in Eastern Siberia: an assessment of the competing effects of CO2 and secondary organic aerosols - Arneth, A.; Makkonen, R.; Olin, S.; Paasonen, P.; Holst, T.; Kajos, M. K.; Kulmala, M.; Maximov, T.; Miller, P. A.; Schurgers, G. (European Geosciences Union, 2016)
Disproportional warming in the northern high latitudes, and large carbon stocks in boreal and (sub)arctic ecosystems have raised concerns as to whether substantial positive climate feedbacks from biogeochemical process responses should be expected. Such feedbacks occur if increasing temperatures lead to e.g. a net release of CO2 or CH4. However, temperature-enhanced emissions of biogenic volatile organic compounds (BVOC) have been shown to contribute to the growth of secondary organic aerosol (SOA) which is known to have a negative radiative climate effect. Combining measurements in Eastern Siberia with model-based estimates of vegetation and permafrost dynamics, BVOC emissions and aerosol growth, we assess here possible future changes in ecosystem CO2 balance and BVOC-SOA interactions, and discuss these changes in terms of possible climate effects. On global level, both are very small but when concentrating on Siberia and the northern hemisphere the negative forcing from changed aerosol direct and indirect effects become notable – even though the associated temperature response would not necessarily follow a similar spatial pattern. While our analysis does not include other important processes that are of relevance for the climate system, the CO2 and BVOC-SOA interplay used serves as an example of the complexity of the interactions between emissions and vegetation dynamics that underlie individual terrestrial feedbacks and highlights the importance of addressing ecosystem-climate feedbacks in consistent, process-based model frameworks.